Nadia Myre, en[counter]s - Tougas, Colette; Couëlle, Marcia; Myre, Nadia (Éditions Art mûr, 2011)
Nadia Myre is a multidisciplinary artist whose work explores themes of language, culture, and memory, and who sources the culture of her Algonquin ancestors as a way of confronting contemporary realities. This monograph provides a comprehensive first look at this Montreal-based artist's remarkable career
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé